Greenhouse Gas Trends. - Sweet, W.
Last year, critics of the Kyoto Protocol glammed onto statistics showing apparently that the Europeans have been less successful than the United States in curtailing the growth of greenhouse-gas emissions. Considered in the context of the Kyoto compliance period starting in 1990 and taking the current membership of the EU into account, Europe has cut its emissions 10.2 percent, while U.S. emissions have increased 16.3 percent. The individual countries that have been most vocal in support of Kyoto have especially reduced their emissions, while emissions have been rising sharply among many of the newer EU members in southern and eastern Europe.
Keywords: Europe emissions; Kyoto Protocol; Kyoto compliance; US emissions; Greenhouse-gas emissions